Graphene oxide-upconversion nanoparticle based optical sensors for targeted detection of mRNA biomarkers present in alzheimer's disease and prostate cancer - Vilela, P; El-Sagheer, A; Millar, T; Brown, T; Muskens, O; Kanaras, A (American Chemical Society, 2016)
The development of new sensors for the accurate detection of biomarkers in biological fluids is of utmost importance for the early diagnosis of diseases. Next to advanced laboratory techniques, there is a need for relatively simple methods which can significantly broaden the availability of diagnostic capability. Here, we demonstrate the successful application of a sensor platform based on graphene oxide and upconversion nanoparticles (NPs) for the specific detection of mRNA-related oligonucleotide markers in complex biological fluids. The combination of near-infrared light upconversion with low-background photon counting readout enables reliable detection of low quantities of small oligonucleotide sequences in the femtomolar range. We demonstrate the successful detection of analytes relevant to mRNAs present in Alzheimer's disease as well as prostate cancer in human blood serum. The high performance and relative simplicity of the upconversion NP-graphene sensor platform enables new opportunities in early diagnosis based on specific detection of oligonucleotide sequences in complex environments.